OPERATIONAL RESILIENCE AND EFFICIENCY OF PRIVATE UNIVERSITIES IN SOUTHWEST NIGERIA: THE COVID-19 PANDEMIC EXPERIENCE - Amos, Nneoma Benita; Dogo, Edafe Bawa; Egwakhe, Johnson A.; Umukoro, Jones E. (APPS Publications, 2022)
The study investigated operational efficiency through operational resilience of private universities in Southwest Nigeria during COVID-19. Private universities were established to impact knowledge, enabled unhindered learning and timely turn-out of graduates since their inception in 1999. However, private universities’ operational efficiency was challenged and truncated by the outbreak of the COVID-19 pandemic, which motivated the thrust to determine their operational resilience along with their efficiency. Primary data were obtained from academic lecturers in eight selected private universities in Southwest Nigeria. The questionnaire used was adapted, and the validity and reliability were established. Findings showed that operational resilience significantly affected the operational efficiency of the universities. Therefore, institutions should leverage technology to enhance response and fast-track learning to drive their operational efficiency in the face of disruptions and pandemic.